1999
DOI: 10.1055/s-1999-42
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Hemostasis in Sphincterotomy-Induced Hemorrhage: Its Efficacy and Safety

Abstract: ES-induced hemorrhage occurred in 10% of the patients studied. The use of needle-knife sphincterotomy and the cutting speed were independent risk factors for the occurrence of bleeding. Once bleeding occurred, its severity was affected by an associated ampullary lesion (impacted stone or cancer) or coagulopathy. Endoscopic hemostasis with epinephrine and/or alcohol was effective and safe in ES-induced hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 17 publications
3
45
2
Order By: Relevance
“…Precutting is also reported to increase the risk of bleeding [2,4,5]. Kim et al reported that sphincterotomy with a needle-knife sphincterotome increased the bleeding rate [23]. In our series, bleeding was seen more frequently in the precutting group but was not observed during precutting.…”
Section: Discussionsupporting
confidence: 42%
“…Precutting is also reported to increase the risk of bleeding [2,4,5]. Kim et al reported that sphincterotomy with a needle-knife sphincterotome increased the bleeding rate [23]. In our series, bleeding was seen more frequently in the precutting group but was not observed during precutting.…”
Section: Discussionsupporting
confidence: 42%
“…11 A plethora of other elements have been shown in either univariate or multivariate analysis as potential risk factors to consider including: precut sphincterotomy, zipper cut, pure cutting current, hemodialysis, cirrhosis, ampullary stone, stone extraction, and papillary stenosis. 5,6,11,22,48,147,151 NSAIDs or aspirin use do not appear to increase the risk of bleeding, however the effect of newer antiplatelet and antithrombotic agents has been less well-studied. 11 The type of energy application during sphincterotomy is also important to consider.…”
Section: Risk Reductionmentioning
confidence: 99%
“…In a prospective study of the risk factors for endoscopic sphincterotomy-induced hemorrhage, Kim et al [46] found that use of the needle-knife sphincterotome caused a higher rate of hemorrhage than the pull-type sphincterotome (P<0.025), as did use of the zipper cut (P<0.049). They also found that, once bleeding occurred, the severity of the bleed was worse with an associated ampullary lesion (impacted stone or cancer) or coagulopathy.…”
Section: Complicationsmentioning
confidence: 99%